Exfoliating effect of β-glycyrrhetinic acid on plaque inducing gingivitis: Comparison with cetylpyridinium chloride - Shinya Kato; Xiangtao Ma; Kayo Sato; Aya Okumura; Nobuo Yoshinari; Akihiro Yoshida (PLoS ONE, 2026)
β-glycyrrhetinic acid (BGA) possesses antibacterial effects against human supragingival plaque bacteria and inhibits biofilm formation. However, the effect of BGA on already formed dental plaque has not been investigated. We analyzed and compared the effects of BGA on preformed supragingival plaque biofilms with those of cetylpyridinium chloride (CPC). All experiments were performed in vitro using biofilms formed by incubating supragingival plaque bacteria for 24 h. First, we analyzed the number of viable and dead bacteria in the biofilms following BGA and CPC application. The number of viable bacteria was significantly reduced by BGA treatment compared with by the solvent control. However, the viable/dead bacterial ratios did not significantly vary. Conversely, the turbidity in the supernatants (optical density at 600 nm [OD 600 ]) was 0.237 ± 0.003, 0.136 ± 0.002, and 0.096 ± 0.002 for the BGA, CPC, and solvent control groups, respectively, indicating superior ability of BGA in biofilm exfoliation. This study suggests that BGA may inhibit dental plaque adhesion and eliminate and disinfect dental plaque through a mechanism different from CPC, contributing to the prevention of periodontal disease.